TECHNICAL IMPROVEMENT PROGRAM MAINTENANCE OF AIRCRAFT USING THE PROCEDURE MSG-3 - A. I. Logvin; D. B. Rychenkov (Научный вестник МГТУ ГА)
This article discusses new approaches to improve the efficiency procedure MSG-3, based on the account of external factors.